Introduction to the Special Issue on Developing Research Methods and Metrics in Macromarketing - Stanton, Julie V.; DeQuero-Navarro, Beatriz; Domegan, Christine; Wooliscroft, Ben (Journal of macromarketing, 2024)
In addition to summarizing the articles included in this Special Issue, this editorial introduction provides a content analysis of 22 years of the Journal of Macromarketing with a focus on quantitative studies. Linking the rich foundation of macromarketing scholarship with novel and purposeful quantitative analysis can provide the evidence needed to help convince policymakers to change the system. Yet macromarketing scholarship has not capitalized in this way on its strengths in explaining marketing and societal connections from a macro perspective. As conceptual models are developed, authors should consider how to support quantitative researchers in extending and testing those models, and all macromarketing scholarship should be purposeful in developing future research agendas that continue their important momentum.